Diagnosing a Diffuse Blistering Rash. Issue 1 (5th January 2022) - Nelson, Jacob; Mengden Koon, Stephanie; Fett, Nicole
ABSTRACT: Blistering dermatoses can be difficult to clinically differentiate. Often extremely unpleasant for patients and potentially life threatening, a prompt and correct diagnosis is paramount. This photo quiz contains information that will aid readers in differentiating various blistering dermatoses.